Borderland, Maquilas, and Feminicide: Issues of Migration and Gendered Violence in Northern Mexico - Alilovic, Lea (Contingent Horizons: The York University Student Journal of Anthropology, 2019)
The rise of maquiladoras, or foreign owned manufacturing plants, in Mexico during the 1970s and 80s symbolizes the social and economic tension of the Mexican–United States borderland. With the implementation of agreements like the Border Industrialization Program (1965) and the North American Free Trade Agreement (1994) that created and supported the transfer of capital and goods between Mexico and the United States, such policies simultaneously limited the movement of people across the border. By the 1990s, growing disparities between the U.S. and Mexico became evident with the mass movement of Mexican economic migrants to the north and the growth of shanty towns south of the border. Women migrants and labourers in particular faced extremely vulnerable positions in the region due to their precarious work and living conditions, substantiated by the paralleling disappearance, kidnapping, and mutilation of women in the borderlands. This article mobilizes Ursula Biemann’s (1999) work on women’s positionality in Mexico to situate their experiences and agency in Mexico’s border town, Ciudad Juarez, within contexts of prevailing feminicide. Ultimately, in engaging in the discussion of the role of what Melissa Wright (2006) calls women’s disposability in the borderlands, this essay will explore why transnational and migrant labour is often overlooked and exploited by policy, leaving women labourers particularly susceptible to such violence.